다양한 공간적 암호화 기법을 적용한 개선된 컬러 영상 워터마킹 기법 - 정수목(Soo-Mok Jung) (한국정보전자통신기술학회 논문지, 2020)
In this paper, we proposed an effective technique for hiding the watermark in the LSB of a color image by applying spatial encryption techniques. Even if the watermark hidden in the LSB of the image is extracted, the information of the extracted watermark cannot be decrypted because the watermark is encrypted using various spatial encryption techniques. Therefore, if the watermark is concealed in the LSB using the spatial encryption techniques proposed in this paper, the security is greatly improved compared to the existing technique of embedding the watermark in the LSB. When watermarking is performed by applying the proposed technique, the image quality of the watermark-concealed image is very good, so it is impossible to distinguish it from the original image, and the watermark, which is confidential data, can be extracted from the watermarked image without loss. The performance of the proposed technique was mathematically analyzed and the superiority of the proposed technique was confirmed through experiments. When the watermark was concealed by applying the proposed technique to Lenna, airplane, Tiffany, and pepper images having a size of 512×512, the PSNR values of the watermarked images were 53.91dB, 54.10dB, 54.09dB, and 54.13dB, respectively. 본 논문에서는 공간적 암호화 기법을 적용하여 컬러 영상의 LSB에 워터마크를 은닉하는 효과적인 기법을 제안하였다. 영상의 LSB에 은닉된 워터마크를 추출하여도 워터마크가 다양한 공간적 암호화 기법을 사용하여 암호화 되어 있기 때문에 추출된 워터마크의 정보를 해독 할 수 없다. 따라서 본 논문에서 제안된 공간적 암호화 기법을 사용하여 LSB에 워터마크를 은닉하면 기존의 LSB에 워터마크를 삽입하는 기법에 비하여 보안성이 크게 향상된다. 제안된 기법을 적용하여 워터마킹을 수행하면, 워터마크가 은닉된 영상의 화질이 매우 우수하여 원본 영상과 구별이 불가능하며 워터마크가 은닉된 영상으로부터 기밀 데이터인 워터마크를 손실 없이 추출 할 수 있다. 제안된 기법의 성능을 수학적으로 분석하고 제안된 기법의 우수성을 실험을 통하여 확인하였다. 512×512 크기를 갖는 Lenna, airplane, Tiffany, pepper 영상에 제안 기법을 적용하여 워터마크를 은닉한 경우, 워터마크가 은닉된 영상의 PSNR 값은 각각 53.91dB, 54.10dB, 54.09dB, 54.13dB 이었다.